Pierwsza podróż lotnicza kardynała Augusta Hlonda (1929) i towarzyszące jej okoliczności - Szczepaniak, Maciej (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
To the abundant bibliography on the activity of Cardinal August Hlond the author of the article wishes to add a reflection on one of his personality traits - interest in aviation. Already in 1929 - so at the very onset of civil aviation in Europe - the Archbishop of Gniezno and Poznań sojourned to Rome by air. The Primate of Poland was probably one of the first cardinals to venture a flight, attracting understandable attention of the mass media. On the basis of archival materials and press information the article traces the cardinal’s journey to Rome for the beatification of the founder of the Salesian Society, Fr. John Bosco. Thanks to the air travel from Poznań via Katowice, Vienna and Venice to Rome, Cardinal Hlond gained the reputation of a progressive person. Realization of the travel schedule was facilitated by such favorable circumstances as the launching of an air connection from Poznań to Katowice during the Polish General Exhibition.